ANALISA INOVASI PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP EFEKTIVITAS JASA SALON CLARA KUTACANE - Sabitah (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
This research is descriptive qualitative, collecting field research data using direct observation and interview methods on the research object to obtain an overview of the research subject. Product Innovation Based on research conducted at several salons in Kutacane, Clara Salon offers 10 (ten) types of Service Product Innovation, meaning that when compared to other beauty salons, Clara Salon is still superior in Service Product Innovation. From this research it can be concluded that Salon Clara has increased in service effectiveness, since its establishment in 2009, until now.